Ultra-light foamed concrete with recycled sand - Ochirbud, Munkhtuvshin; Hong, Kyungchan; Kang, Suah; Kim, Youngho; Ha, Sangsu; Choi, Donguk (Journal of Asian Concrete Federation, 2022)
Carbon neutralization and upcycling of recycled resources in concrete and construction industry are key themes of sustainability. In this study, ultra-light foamed concrete (ULFC) was fabricated using high early strength Portland cement, silica fume, fly ash, and recycled fine aggregates. ULFC with dry density as low as 284 kg/m3 was fabricated by chemical foaming method using hydrogen peroxide (H2O2) as the foaming agent and hydroxypropyl methyl cellulose ether (HPMC) as the foam stabilizer. Thermal conductivity of the ULFC was 0.092 W/mK. The potential application of the ULFC fabricated in this study is the inorganic insulating material with low density, low thermal conductivity, and good fire resistance for fabric reinforced cementitious matrix (FRCM) building sandwich panels.